(untitled) (Comparatismi, 2017)
In fictional texts, personal names (and more generally proper nouns) are considered to be meaningful linguistic and cultural items since they often convey specific connotations to a literary text, and they constitute a challenge for translators since they are usually used to define the character itself, often from an ironic perspective. Translators can adopt different strategies (copy; naturalization; transcription; addition; phonological replacement; re-creation; cultural transplantation) but, as it often happens in translation, a significant part of specific connotations of the name is usually lost. Flann O’Brien resorts to a “creative” use of proper names, often comments them (De Selby, one of his characters, claims “to be in a position to state the physiological ‘group’ of any person merely from a brief study of the letters of his name”). This study analyses O’Brien’s use of proper nouns and the several solutions adopted by translators of his novels and short stories, suggesting some possible alternatives and highlighting the semantic potential of the examined proper names which is inevitably lost.